0564 Sleep patterns of patients on home parenteral nutrition: a home-based observational study. (25th May 2022) - Dashti, Hassan; Godbole, Meghna; Chen, Angela; Mogensen, Kris; Leong, Aaron; Burns, David; Winkler, Marion; Saxena, Richa; Compher, Charlene
Abstract: Introduction: Whereas home parenteral nutrition (HPN), a form of nutrition administered through a central venous catheter for patients with intestinal failure, is necessary for survival, the current standard practice for HPN is to administer infusions for approximately 12-hour periods overnight, coinciding with nighttime sleep. Patients supported with HPN often report poor sleep, however limited research has been conducted to objectively measure sleep patterns of HPN-dependent patients. Methods: We aimed to characterize the sleep patterns of patients on HPN through 7-day actigraphy in a remote, home-based observational study. Sleep measures of clinical importance were derived from actigraphy including sleep duration, sleep efficiency, sleep onset latency, and wake after sleep onset. Participants also completed validated sleep surveys electronically. Results: 20 participants completed all study procedures [mean (standard deviation): age =51.6 (13.9), BMI =21.4 kg/m2 (4.6), 80% female]. The population median (interquartile range) for sleep duration, sleep efficiency, sleep onset latency, and wake after sleep onset was 6.9 (1.1) hours, 83.3 (7.8) %, 11.8 (7.1) minutes and 57.2 (39.9) minutes, respectively, and 55%, 60%, 35%, and 100% of participants did not meet the recommendations for these measures from the National Sleep Foundation. 65% of participants reported napping at least once during the 7-day period. Based on the Insomnia Severity Index, 70% of participants were classified as having sub-threshold or more severe insomnia. Based on the Pittsburgh sleep quality index, 85% were classified as having significant sleep disturbance. Conclusion: Most HPN-dependent patients likely have disrupted sleep largely driven by difficulty maintaining sleep. The extent to which overnight HPN infusions contributed to poor sleep cannot be elucidated from this observational study. Addressing known factors that contribute to poor sleep and encouraging sleep hygiene and sleep interventions are imperative to improve the overall quality of life of patients requiring HPN. Support (If Any): Research reported in this publication was supported by the American Society for Parenteral and Enteral Nutrition (ASPEN) Rhoads Research Foundation.